Produção de géis porosos por congelamento - Gonçalves, Jeniffer Silveira (2018)
The work presented here had as a proposal the development of a process adapted from the ice-template technique, using as solute sodium alginate an organic polymer of renewable and non-toxic source, which forms structures due to its crosslinking ability when in contact with divalent ions, such as Ca2+. The use of renewable polymers together with low cost processes for obtaining porous materials has great relevance for the development of a sustainable economy. The objective was to promote the simplification of the ice-template process, with lower cost for the technique from a freezing system, without the use of the lyophilization technique and the insertion of the gel into porous materials. The formed gels were submitted to drying by apolar solvents, morphological characterization by optical microscopy and scanning electron microscopy (SEM), and porosity and capillary tests. It has been determined that it is possible to produce porous materials through calcium alginate formulations in a simple manner, forming multidirectional and unidirectional pore materials. The formulation of 0,15 g/100g of sodium alginate with 0,0010 mol/L of CaCl2 was the best so far, to be used in the formation of porous gels, because of the best mass yield. Drying with the use of butanol was the one that best maintained the structural integrity of the gels and the coffee composites besides helping the gel structure, allowed the prospection for new applications to the gels produced. We have proven the concept of permeating the freezing formulation in porous materials and producing freezing gels inside their pores